Pedagogic Competence of Arabic Language Teachers in Increasing the Interest and Learning Achievement of Grade IV Students of Madrasah Ibtidaiyah Al Munawaroh Kaliruyung Bantarbolang District Pemalang Regency - Khaerudin, Khaerudin; Maufur, Maufur; Nasukha, Munthoha (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the pedagogic competence of Arabic teachers at Madrasah Ibtidaiyah (MI) Al Munawaroh Kalirueung, Bantarbolang District, Pemalang Regency and its impact on the interests and learning achievements of grade IV students. This study uses a qualitative descriptive approach with a case study method. Data were collected through participatory observation, in-depth interviews, and document analysis. The results of the study show that Arabic teachers at MI Al Munawaroh have good pedagogic competence, including the ability to plan, implement, and evaluate learning. The implementation of effective pedagogic competencies is positively correlated with an increase in students' interest in learning, as seen from active participation and enthusiasm. In addition, students' learning achievement also showed a significant increase. This study recommends the importance of continuous teacher professional development to maintain and improve the quality of pedagogic competence for the optimization of Arabic language learning.